The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.22230/cjc.2021v46n4a3807
|View full text |Cite
|
Sign up to set email alerts
|

The Representation of Syrian Refugees in Canadian Online News Media: A Focus on the Topos of Burdening

Abstract: Background: This study focuses on the representation of Syrian refugees in Canadian online news media. It examines 375 articles selected from three of the most visited Canadian news sites, namely the Toronto Star, which favours the Liberal Party, and the Toronto Sun and National Post, which favour the Conservative Party. Analysis: The basis of this research is a topoi analysis, whereby instances of the topos of burdening are identified, examined, and categorized as either positive or negative. Conclusion and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The above-mentioned studies provide invaluable insights into the depiction of Syrian refugees in Canadian media; nevertheless, a more linguistically-grounded analysis is needed because ‘in texts, we may be aware of what the speaker or author is doing, but not so much how they are doing this’ (Machin and Mayr, 2012: 5). Also, in contrast to previous studies, which utilized a purely qualitative approach (Mustafa et al, 2021), the current study merges quantitative and qualitative tools and methods of Corpus Linguistics (CL) and Critical Discourse Analysis (CDA) to examine the data from bottom-up and top-down perspectives, respectively. A corpus-assisted approach enables the analyst to have a thorough understanding of ‘the meanings and functions of certain lexical choices made in texts about refugees’ (Baker and McEnery, 2005: 223), while CDA is used to critically examine the micro-structures of the text and tries to interpret the findings in the social context, maintaining that discourse is both ‘socially constitutive as well as socially conditioned’ (Fairclough and Wodak, 1997: 258).…”
Section: Refugees In the Newsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above-mentioned studies provide invaluable insights into the depiction of Syrian refugees in Canadian media; nevertheless, a more linguistically-grounded analysis is needed because ‘in texts, we may be aware of what the speaker or author is doing, but not so much how they are doing this’ (Machin and Mayr, 2012: 5). Also, in contrast to previous studies, which utilized a purely qualitative approach (Mustafa et al, 2021), the current study merges quantitative and qualitative tools and methods of Corpus Linguistics (CL) and Critical Discourse Analysis (CDA) to examine the data from bottom-up and top-down perspectives, respectively. A corpus-assisted approach enables the analyst to have a thorough understanding of ‘the meanings and functions of certain lexical choices made in texts about refugees’ (Baker and McEnery, 2005: 223), while CDA is used to critically examine the micro-structures of the text and tries to interpret the findings in the social context, maintaining that discourse is both ‘socially constitutive as well as socially conditioned’ (Fairclough and Wodak, 1997: 258).…”
Section: Refugees In the Newsmentioning
confidence: 99%
“…For example, Tyyskä et al (2017) identified frequent descriptions of Syrian refugees as vulnerable and lacking agency, while Syrian men were specifically highlighted as would-be terrorists in disguise. Although the tone of the coverage became softer and more humanizing after the emergence of the Kurdi photo (Wallace, 2018), another study found that in conservativeleaning newspapers, Syrian refugees were depicted as a burden on the healthcare system and housing resources, demonstrating the role of ideological stances of the news sources in their representations (Mustafa et al, 2021).…”
Section: Refugees In the Newsmentioning
confidence: 99%